Penelitian terhadap Dapur Mami Icha: Catering UMKM yang Mengutamakan Kualitas dan Kepuasan Pelanggan (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This study focuses on prioritizing quality and customer satisfaction as the key to the success of the Dapur Mami Icha Catering MSME in Medan, North Sumatra. This business, which started with a small capital, has succeeded in building a reputation through serving delicious, healthy, and affordable food menus, as well as friendly and personal service. The strategy for retaining customers is carried out through a direct communication approach, such as reminders to order before the event day, and price adjustments according to customer needs. In addition, innovation in menu development and consistency in quality are the main factors that make customers loyal and recommend this service. Collaboration with similar business actors also strengthens the competitiveness and capacity of the business. The success of Dapur Mami Icha confirms that focusing on product quality and customer satisfaction is an important foundation in building a sustainable and competitive MSME business in the local catering market.